Development and Evidence of the Validity of the Condom Use Attitudes Scale for Youth and Adults in a Chilean Context - Ferrer-Urbina, Rodrigo; Mena-Chamorro, Patricio; Sepúlveda-Páez, Geraldy; Carmona-Halty, Marcos (Frontiers in Psychology, 2021)
Condom use is the most effective preventive behavior against HIV transmission, and its inadequate use is a public health problem that occurs mostly among youth and young adults. Although there are scales that measure condom use, those that exist correspond to English-speaking developments or do not have psychometric evidence to support them, so it is possible that the available adaptations of instruments do not adequately reflect the phenomenon in the Chilean population. Thus, the study aims to develop a scale to assess attitudes towards condom use in Chilean youth and young adults. Initially, a sample of students between 18-39 years (n = 520) was used for debugging the instrument. Then, a second sample was taken from the general population aged 18-40 (n = 992) to confirm the factor structure of the proposed model. The final scale has 10 items and 3 attitudinal dimensions (affective, cognitive, and behavioral). The results show that the identified structure provides adequate levels (ω > .7) or at least sufficient of reliability (ω > .6) and presents evidence of validity, based on the internal structure of the test, through ESEM (CFI = .993; TLI = .984; RMSEA = .056). In addition, evidence of validity was obtained based on the relationship with other variables and strong invariance between the scores of men and women. It is concluded that the scale developed has adequate psychometric properties to assess, in brief form, condom use attitudes in equal samples for research and screening purposes.